Development of an Islamic guidance and counseling module based on ethical behavior values to prevent risky social behavior among students - Askolani, Febrina (Tawazun: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the need for developing an Islamic Guidance and Counseling Module based on ethical behavior values to prevent free association among junior high school students, to formulate the module design, and to examine its feasibility. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through needs assessment questionnaires distributed to guidance and counseling teachers, document analysis of existing modules, and expert validation sheets covering linguistic, counseling, Islamic education, and design aspects. The needs analysis revealed that 100% of teachers expressed the necessity of a module integrating Islamic ethical values, while 25% had not yet possessed similar instructional materials. The developed module comprises five thematic chapters addressing causes, impacts, and preventive strategies grounded in Islamic teachings. Feasibility testing yielded an average score of 88.9%, categorized as “Highly Feasible.” These findings indicate that the module is appropriate for use in Islamic guidance and counseling services to strengthen ethical awareness, reinforce religious character, and support preventive efforts among junior high school students. Abstrak Penelitian ini bertujuan untuk menganalisis kebutuhan pengembangan Modul Bimbingan dan Konseling Islam berdasarkan nilai-nilai perilaku etis guna mencegah pergaulan bebas di kalangan siswa sekolah menengah pertama, merumuskan desain modul, serta menguji kelayakannya. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan (R&D) dengan menerapkan model ADDIE, yang terdiri dari tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Data dikumpulkan melalui kuesioner penilaian kebutuhan yang dibagikan kepada guru bimbingan dan konseling, analisis dokumen modul yang sudah ada, serta lembar validasi ahli yang mencakup aspek linguistik, konseling, pendidikan Islam, dan desain. Analisis kebutuhan menunjukkan bahwa 100% guru menyatakan perlunya modul yang mengintegrasikan nilai-nilai etika Islam, sementara 25% di antaranya belum memiliki bahan ajar serupa. Modul yang dikembangkan terdiri dari lima bab tematik yang membahas penyebab, dampak, dan strategi pencegahan yang didasarkan pada ajaran Islam. Uji kelayakan menghasilkan skor rata-rata 88,9%, dikategorikan sebagai “Sangat Layak.” Temuan ini menunjukkan bahwa modul ini sesuai untuk digunakan dalam layanan bimbingan dan konseling Islam guna memperkuat kesadaran etika, memperkuat karakter keagamaan, dan mendukung upaya pencegahan di kalangan siswa sekolah menengah pertama.